Do Emergency Medicine Residency Graduates Feel Prepared to Manage Closed Fractures After Training?. (January 2017) - Pittman, Mark A.; Yarris, Lalena M.; Lall, Michelle D.; Smith, Jessica L.; Wills, Charlotte P.; Ufberg, Jacob W.; Hegarty, Cullen B.; Love, Jeffrey N.
Abstract: Objectives: Fractures comprise 3% of all emergency department (ED) visits. Although emergency physicians are often responsible for managing most of the initial care of these patients, many report a lack of proficiency and comfort with these skills. The primary objective was to assess how prepared recent emergency medicine (EM) residency graduates felt managing closed fractures upon completion of residency. Secondary objectives included whether residency training or independent practice contributed most to the current level of comfort with these procedures and which fractures were most commonly reduced without orthopedic consultation. Methods: An anonymous online survey was sent to graduates from seven EM residency programs over a 3‐month period to evaluate closed fracture reduction training, practice, and comfort level. Each site primary investigator invited graduates from 2010 to 2014 to participate and followed a set schedule of reminders. Results: The response rate was 287/384 (74.7%) and included 3‐year (198/287, 69%) and 4‐year (89/287, 31%) programs. Practice in community, academic, and hybrid ED settings was reported by 150/287 (52.3%), 64/287 (22.3%), and 73/287 (25.4%), respectively. It was indicated by 137/287 (47.7%) that they reduce closed fractures without a bedside orthopedic consultation greater than 75% of the time. The majority of graduates felt not at all prepared (35/287, 12.2%) or somewhat prepared (126/287, 43.9%) upon residency graduation. Postresidency independent practice contributed most to the current level of comfort for 156/287 (54.4%). The most common fractures requiring reduction were wrist/distal radius and/or ulna, next finger/hand, and finally, ankle/distal tibia and/or fibula. Conclusions: Although most recent graduates feel at least "somewhat" prepared to manage closed fractures in the ED, most felt that independent practice was a greater contributor to their current level of comfort than residency training. Recent graduates indicate that fracture reduction without orthopedic consultation is common in today's clinical practice. This survey identifies common fractures requiring reduction which EM residencies may wish to consider prioritizing in their emergency orthopedic curricula to better prepare their residents for independent clinical practice.